2022
DOI: 10.1371/journal.pone.0263518
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying volume and high-speed technical actions of professional soccer players using foot-mounted inertial measurement units

Abstract: Aims The aims of the study were two-fold: i) examine the validity and reliability of high-speed kicking actions using foot-mounted inertial measurement unit’s (IMU), ii) quantify soccer players within-microcycle and inter-positional differences in both the frequency and speed of technical actions. Methods During the in-season phase (25 weeks) of the UK domestic season, 21 professional soccer player ball releases, high-speed ball releases and ball release index were analysed. Pearson product-moment correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…MD-1, MD-5), playing position and training type (small sided game vs tactical drills) on the aforementioned technical parameters. Furthermore Lewis 29 observed MD + 1 having the highest absolute ball releases compared to all other training days, a decrease in frequency of ball releases as training becomes closer to match days, MD-1 and MD + 1 having the highest number of absolute and relative high-speed ball releases with variability being impacted by the type of drill or practice that the players were participating in. It thus is likely that different technical demands may be evident across different tiers of football and within different club settings.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…MD-1, MD-5), playing position and training type (small sided game vs tactical drills) on the aforementioned technical parameters. Furthermore Lewis 29 observed MD + 1 having the highest absolute ball releases compared to all other training days, a decrease in frequency of ball releases as training becomes closer to match days, MD-1 and MD + 1 having the highest number of absolute and relative high-speed ball releases with variability being impacted by the type of drill or practice that the players were participating in. It thus is likely that different technical demands may be evident across different tiers of football and within different club settings.…”
Section: Discussionmentioning
confidence: 88%
“…Where there is reduced locomotor activity exposure, coaches lose the ability to provide 'top up' sessions within this hybrid loan system due to competing priorities for the primary and the host club. 29 To overcome such limitations, clubs in Spain use 'Colt' Squads or B teams to further the development opportunities of their transitioning players who represent their home club whilst playing in a lower division. 30 When comparing the professional progression of the players involved in the B team, Los Acros 17 showed that the players who had been signed internally from the club progressed at a rate of 43% versus 30% of players who were signed directly into the B squad.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations